Monetary Transmission in Developing Countries : Evidence from India - Mishra, Prachi (IMF Working Papers; Working Paper ;, 2016)
We examine the strength of monetary transmission in India, using a conventional structural VAR methodology. We find that a tightening of monetary policy is associated with a significant increase in bank lending rates and conventional effects on the exchange rate, though pass-through to lending rates is only partial and exchange rate effects are weak. We could find no significant effects on real output or the inflation rate. Though the message for the effectiveness of monetary transmission in India is therefore mixed, our results for India are more favorable than is often found for other developing countries.